Computing Marine Plankton Connectivity under Thermal Constraints - Manral, Darshika (Utrecht University, 2023)
Data generated for manuscript 'Computing Marine Plankton Connectivity under Thermal Constraints' submitted to Frontiers in Marine Science, section Marine Ecosystem Ecology on 10 October 2022. The data consists of release locations file and mapping of locations to Lagrangian simulations, connectivity matrices, matrices from bootstrapping results and between sample station connectivities. The repository with the code to run the generate release locations, simulations and analysis is available at https://github.com/OceanParcels/atlanteco_tara_connectivity_plankton.
Keywords: Natural Sciences - Earth and related environmental sciences (1.5); Lagrangian connectivity, marine plankton, Atlantic Ocean